BUILDING A JOINT COMMITMENT FOR THE IMPLEMENTATION OF SUSTAINABLE ISLAMIC EDUCATION QUALITY MANAGEMENT - Astuti, Siwi; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Cakrawala Pedagogik, 2024)
Improving the quality of Islamic education in a sustainable manner requires joint commitment from all stakeholders. This article discusses the importance of building joint commitment and implementing Sustainable Islamic Education Quality Management. Sustainable Islamic Education Quality Management is a systematic and structured approach to ensure that Islamic educational institutions consistently and sustainably meet or even exceed the needs and expectations of their stakeholders. This article explains the steps to build joint commitment, strategies for strengthening commitment, the benefits of implementing Sustainable Islamic Education Quality Management, and strategies for overcoming challenges in its implementation. In conclusion, building a joint commitment and implementing Sustainable Islamic Education Quality Management is very important to improve the quality of Islamic education. With the right strategy, Sustainable Islamic Education Quality Management can be implemented successfully and provide benefits for all stakeholders.